ANALISIS PENGADAAN BARANG DAN JASA SECARA ELEKTRONIK (E-PROCUREMENT) PADA LPSE KOTA KENDARI - Arsyad, Maharany; Suriadi, La Ode; Anam, Syamsul (JURNAL EKONOMI UHO, 2016)
This study aimed to describe various data obtained regarding the efficiency and effectiveness of e-procurement in the procurement of goods and services that are run by LPSE Kendari. The analytical method used is descriptive analysis provides a description or explanation of the procurement of goods and services electronically (e-procurement), which is run by LPSE Kendari by using primary data in the form of data obtained directly from contractors, consultants, and working groups unit procurement services (POKJA ULP) using a questionnaire to obtain necessary information. In this case the perception of the parties directly involved with the implementation of e-procurement is needed to determine the extent to which opinions, ratings, views, or their attitude towards the implementation of e-procurement in LPSE Kendari and secondary data such as figures include the value of HPS, the value of contract is, and list of packages when the auction in October, November, and December of 2014. The results showed that the implementation of e-procurement in Kendari in October-December 2014 was run efficiently in terms of cost and time. This is demonstrated which can save costs in a budget area of Kendari and the procurement of goods / services can be completed before the deadline specified from the ULP. Besides e-procurement also increase the effectiveness with which the average value based on the Likert scale that is based on the responses of the contractor, consultants and WG ULP approved e-procurement to enhance transparency, accountability, and access to markets and competition with some input in each variable.